Dose gradient impact on equivalent dose at 2 Gy for high dose rate interstitial brachytherapy - Hannoun-Levi, Jean-Michel (Termedia Publishing House, 2012)
PURPOSE: To evaluate a new calculation model estimating the equivalent dose at 2 Gy (EQD2) taking into account dose gradient in high dose rate interstitial brachytherapy (HDRIB). MATERIAL AND METHODS: Forty dose-volume histograms (DVHs) of breast (20 pts) and prostate (20 pts) cancer dose distributions were reviewed. Physical prescribed doses (PPD) were 34 Gy (10f/5d) and 18 Gy (6f/2d) for breast (partial irradiation protocol) and prostate (boost after external irradiation) treatment, respectively. For each DVH, clinical target volume (CTV), V100, V150, V200, D90 and D100 were determined. Based on DVH segmentation, elementary doses (d) delivered to elementary volumes were determined, then multiplied by C (% of CTV receiving d). According to the linear quadratic model, EQD2 was calculated for different α/β ratios. RESULTS: For breast implant, median EQD2 (α/β = 4) was 42 Gy and 76 Gy (66-85) without and with dose gradient consideration, respectively. For prostate implant, median EQD2 (α/β = 1.5) was 39 Gy and 98 Gy (90-103) whether dose gradient was not or was taken into account, respectively. CONCLUSIONS: This study pointed out that for brachytherapy, EQD2 calculation must take into account the dose gradient. Because this model is a mathematical one, it has to be cautiously applied. Nevertheless, it appears as a useful tool for EQD2 comparison between the same PPD delivered through EBRT or brachytherapy regarding trial result interpretation.